COMPARING TWO DIFFERENT INSTRUCTOR-RATERS IN ASSESSING EFL STUDENTS’ PARAGRAPH WRITINGS: AN ACTION RESEARCH - Syayid Sandi Sukandi; Riny Dwitya Sani (Journal of Language, Literature and Teaching, 2020)
A grade that students received after learning a writing course determines their writing performance in the course. Quite rare for writing instructors, especially those who teach in the EFL setting in a parallel classroom setting of more than one, to reflect on what does it mean to assess a piece of writing composed by EFL students. Therefore, this research was conducted to investigate the aspect above. It is action research in nature. Data were collected from 102 students’ final examination answer sheets. The instrument used is analytical scoring rubrics. Findings show that the different raters might show a similar pattern of using the scoring rubrics, but the tendency of arriving at the same conclusion for each item in the scoring rubrics is low.